2021
DOI: 10.3390/plants10102199
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Two Thymelaeaceae Species: Daphne mucronata Royle and Thymelaea hirsuta (L.) Endl

Abstract: Daphne mucronata Royle and Thymelaea hirsuta (L.) Endl both belong to the Thymelaeaceae family. Both species are used traditionally to treat several diseases along with various daily applications by Jordanian Bedouins. Traditionally, those species are identified through personal proficiency, which could be misleading due to human errors or lack of expertise. This study aims to investigate an effective DNA barcoding method to identify and characterize Daphne mucronata Royle and Thymelaea hirsuta plant species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The DNA barcoding technique has been proven to be an effective tool for distinguishing medicinal plant species (Al-Qurainy et al, 2011;Khan et al, 2017;Alkaraki et al, 2021). However, this study revealed that the nuclear ITS and the chloroplast psbA-trnH and trnL-trnF barcodes had a low capacity for identifying C. lodarensis at the molecular level.…”
Section: Discussionmentioning
confidence: 78%
“…The DNA barcoding technique has been proven to be an effective tool for distinguishing medicinal plant species (Al-Qurainy et al, 2011;Khan et al, 2017;Alkaraki et al, 2021). However, this study revealed that the nuclear ITS and the chloroplast psbA-trnH and trnL-trnF barcodes had a low capacity for identifying C. lodarensis at the molecular level.…”
Section: Discussionmentioning
confidence: 78%